The bone quality of female elite cyclists is characterized by impaired microarchitecture of cortical and trabecular bone as assessed by high-resolution peripheral computed tomography (HR-pqct) - Hilkens, L.; van den Bergh, J.; Bevers, M.; Wyers, C.; van Loon, L.; van Dijk, J. W. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Accumulating evidence indicates that many elite road-race cyclists have low areal bone mineral density (aBMD) as assessed by dual-energy X-ray absorptiometry (DXA). However, aBMD data does not provide information on bone quality, such as microstructural features of both cortical and trabecular bone, or bone strength. The present study aimed to assess aBMD, volumetric BMD (vBMD), bone microarchitecture, and bone strength in elite road-race cyclists. METHODS: In this ongoing cross-sectional study, 20 female elite road-race cyclists (21±2 y; 59.8±6.1 kg; BMI 20.8±1.6 kg/m2) underwent DXA for the assessment of aBMD and high-resolution peripheral computed tomography (HR-pQCT) for the assessment of vBMD and bone microarchitectural parameters at the distal tibia and radius, respectively. Finite element analysis modelling was conducted to calculate bone strength. Z-scores were calculated for all outcomes, with Z-scores < -1 interpreted as low bone density or impaired bone microarchitecture. Data are presented as mean±SD and percentages. RESULTS: With a mean Z-score of *0.3±0.9 and -0.9±1.1, low aBMD was present in 25 and 35% of the participants at the femoral neck and lumbar spine, respectively. Total vBMD of the tibia (296±39 mg/cm3) and radius (304±42 mg/cm3) was low in 40 and 45% of the participants, respectively. Low cortical vBMD was found in 35 and 40%, and low trabecular vBMD in 25 and 15% of the participants at the tibia and radius, respectively. At the tibia, 60% of the participants had a low cortical thickness (1.24±0.20 mm), 40% had low trabecular thickness (0.25±0.02 mm) and 30% had low trabecular number (1.33±0.19 trabeculae/mm). The findings at the distal radius were less pronounced, although 25% of the participants had a low cortical thickness. Calculated bone strength (failure load) was low in 20 and 15% of the participants at the tibia (8759±1522 N) and radius (3110±661 N), respectively. CONCLUSION: Bone health of female elite road-race cyclists was characterized by low aBMD as measured by DXA, but also low vBMD as measured by HR-pQCT. The bone quality of elite road-race cyclists is particularly characterized by reduced cortical thickness and impaired trabecular microarchitecture at the tibia. Calculated bone strength was also affected, but to a lesser extent.